ANALISIS TINGKAT RISIKO KELELAHAN PADA MASINIS COMMUTER LINE RUTE BOGOR-JAKARTA KOTA - Adhinda Lili Pramasari; Baju Widjasena; Bina Kurniawan; Suroto Suroto (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2017)
Fatigue is one of the main factors of accident involving public transportation drivers, one of them is train drivers. Rail accident data summarized by the NTSC, railway accidents in Indonesia during 2007 until 2013 as many as 46 accidents. Total hours of sleep and quality of sleep obtained during the period of time when a person is not working can affect recovery from fatigue. The purpose of this research is to identify fatigue hazard and analyze fatigue risk level, so that the appropriate control can be determined. Variables studied include working hours, work shift, workload, work environment, rest time, sleep disturbance, physical condition and stress. Identification of fatigue hazard and analysis of fatigue risk level conducted to each variable. Identification of fatigue hazard was conducted by observation and indepth interview. The subjects of this study amounted to 5 as key informants and 3 as triangulation informants. Analysis of fatigue risk level was conducted by qualitative method and calculated with crossing consequences level and likelihood level. The results showed the entire train driver interviewed professed often experience fatigue. Symptoms of fatigue are often perceived by the five train drivers interviewed are drowsiness, feeling thirsty, pain in the waist, and the onset of bored. Tracks train long and monotonous as well as the extension of working hours (overtime) that they naturally contribute greatly to fatigue experienced. The conclusion of this study is is that fatigue is one of the problems that can occur on a commuter line train drivers. Companies need to provide training to train drivers on knowledge to recognize fatigue, factors that contribute to the onset of fatigue, the effects of fatigue and how to overcome the fatigue at the time of on duty.